The Immunological Response of Hiv-Positive Patients Initiating Haart at the Komfo Anokye Teaching Hospital, Kumasi, Ghana - Annison, L (Ghana Medical Association, 2013)
OBJECTIVE: The study sought to document the experience of immunological improvement among Ghanaian PLHIV on HAART comparing different categories of patients. SETTING: Serology Unit, Komfo Anokye Teaching Hospital, Kumasi, Ghana. PARTICIPANTS: The study comprised a convenient sample of 303 treatment naïve HIV patients due to start HAART. METHODS: Questionnaires were used to collect patient demographic and clinical data. Four CD4 counts were measured at six-monthly intervals to determine rates of CD4 change. These were pre-therapy, 1(st) post-therapy, 2(nd) post-therapy, and 3(rd) post-therapy counts. The rates of CD4 change among the different categories of patients were also compared. RESULTS: At baseline, women had higher CD4 count (mean of 77.4cells/°l), and mean age of participants was 40 years. The CD4 count increased from a mean baseline of 70.2 cells/°l to 229.2, 270.0, and 297.6 cells/°l at 6, 12, and 18 months of treatment respectively (P <0.0001 at each time point). There were no gender (P=0.46) and age (P=0.96) differences in treatment response. There was no difference (P=0.18) in treatment response comparing those with CD4 <250 cells/°l and those whose CD4 count was between 250 and 350 cells/°l at baseline although patients with baseline CD4 count <250 cells/°l showed larger increases after 12 months of treatment. Out of 282 patients with pre-therapy CD4 count "250 cells/°l, 241 (85.5%) and 41 (14.5%) were adherents and nonadherents respectively. Mean rate of increase was 15.2 and 8.4 cells/°l/month in adherent and non-adherent patients respectively (p=0.2). CONCLUSION: The study suggests that a sustained CD4 increase could be achieved in adherent patients commencing therapy with baseline CD4 count ≤250 cells/°l, and that these patients have greater ability for immunological recovery during 12 months of treatment The study, therefore, concludes that significant immunological improvement is possible among Ghanaian PLHIV on HAART as long as a high level of treatment adherence is observed.